2021
DOI: 10.1051/0004-6361/202140566
|View full text |Cite
|
Sign up to set email alerts
|

The X-CLASS survey: A catalogue of 1646 X-ray-selected galaxy clusters up to z ∼ 1.5

Abstract: Context. Cosmological probes based on galaxy clusters rely on cluster number counts and large-scale structure information. X-ray cluster surveys are well suited for this purpose because they are far less affected by projection effects than optical surveys, and cluster properties can be predicted with good accuracy. Aims. The XMM Cluster Archive Super Survey, X-CLASS, is a serendipitous search of X-ray-detected galaxy clusters in 4176 XMM-Newton archival observations until August 2015. All observations are clip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…In addition to ROSAT, the XMM-Newton and Chandra observatories are also widely used to identify galaxy clusters. With improved resolution and sensitivity, as well as longer exposure times, they could identify faint clusters at high redshift, as shown, for instance, in the works of Mehrtens et al (2012), Clerc et al (2012Clerc et al ( , 2016, Takey et al (2011Takey et al ( , 2013Takey et al ( , 2014Takey et al ( , 2016, Pacaud et al (2016), Koulouridis et al (2021).…”
Section: Introductionmentioning
confidence: 89%
“…In addition to ROSAT, the XMM-Newton and Chandra observatories are also widely used to identify galaxy clusters. With improved resolution and sensitivity, as well as longer exposure times, they could identify faint clusters at high redshift, as shown, for instance, in the works of Mehrtens et al (2012), Clerc et al (2012Clerc et al ( , 2016, Takey et al (2011Takey et al ( , 2013Takey et al ( , 2014Takey et al ( , 2016, Pacaud et al (2016), Koulouridis et al (2021).…”
Section: Introductionmentioning
confidence: 89%
“…As eFEDS and the XXL surv e y were taken in different parts of the sky there are no clusters in common. Although we note that the X-CLASS analysis of the XMM archive (up to 2015 August) that made use of the XXL pipelines does contain some eFEDS candidates (Koulouridis et al 2021 ). Comparisons are limited to ensemble distributions of the cluster samples.…”
Section: O M Pa R I S O N O F T H E E F E D S O P T I C a L Ly C O N ...mentioning
confidence: 99%
“…Second, we combined several large cluster catalogues (Abell et al 1989;Piffaretti et al 2011;Rykoff et al 2014;Wen et al 2012;Wen et al 2018;Zou et al 2021;Koulouridis et al 2021), and check if any clusters serendipitously observed in XMM-Newton observations in the released dataset. The instrument mode for the MOS1 and MOS2 is set as "FULL FRAME", and the modes "FULL FRAME", "EXTENDED FULL FRAME" and "LARGE WINDOW" are chosen for the EPN sytem.…”
Section: Galaxy Clusters In X-ray Data Archivesmentioning
confidence: 99%